The Problem of Human Identity in Gogol’s Works - Rolik, A. V.; Plotnikov, Y. O. (Видавництво НДУ ім. М. Гоголя, 2023)
Andreas Larson’s monograph «Gogol and The Problem of Human Identity» emphasizes that the problem of human identity runs through all of Gogol’s work as a red thread. It also highlights that Gogol’s views on life in his literary works are veiled and can only be identified in a broad context. A. Larson underlines, that from his earliest years Gogol was looking for an occupation that could benefit people and managed to show his comic talent with the success of «Evenings on a farm near Dikanka». Since then, he was considered a comic author. However, at that time, Gogol still thought that his fantastic worlds had to seem comical to readers for the same reasons they appeared so to him. Only after the audience’s reaction to the comedy «The Government Inspector» showed that even the way his friends reacted to this piece differed a lot from what he had predicted, Gogol began to doubt the power of laughter. From that moment, he was becoming more and more didactic. Gogol hoped that «The Government Inspector» would have a greater impact on people than the stories he wrote, as he considered the theatre as a means of mass influence. In the bizarre world of comedy based on the incorrect identification of actors, Gogol clearly defines laughter as the only positive character in the play. Therein lies his theory of the didactic effect of the comic grotesque. Only with the help of laughter readers can free themselves from the grotesque, step aside and break its bonds. Gogol endowed his characters with such features that, despite the total absence of positive qualities, they were similar to real people. In this way, he hoped that the audience would be able to identify with these characters and by breaking the shackles of the grotesque they would get rid of their shortcomings, vices, and inferiority. According to A. Larson, his mistake consisted in the fact that the vast majority of the public had a completely different starting point of view in world perception than Gogol. Gogol defined the plot of his work as the «soul of man». At the same time, the German researcher claims, he knew for sure neither his own personality nor, even more so, the ideal personality of a person. He consistently strengthened realistic didactic elements in his works to force the reader to accept the author’s point of view. Thus, according to A. Larson, Gogol raped himself.
Keywords: Gogol; identity; creativity; humour; laughter; grotesque; comedy; realistic elements; worldview; search